Penyelesaian Sengketa Tanah Berstatus Hak Milik Dijadikan Akses Jalan bagi Pemilik Tanah yang Terkurung - Dewi Sulistianingsih; Mohammad Katerina Ronaldi; Mochammad Shidqon Prabowo; Yuli Prasetyo Adhi (Mahalini: Journal of Business Law, 2024)
The purpose of this study is to determine how the rights of the community whosehouses do not have access roads due to being surrounded by other houses areprotected and to analyze the resolution of disputes over land that will be used asaccess roads. One manifestation of the social function contained in the BasicAgrarian Law is the obligation of landowners to provide access roads to landownerswho are surrounded or blocked by their land. However, in reality, legal problemsoften arise on land with private ownership status that will be used as access roads.This research uses an empirical juridical method with a case study approach relatedto land disputes that will be used as access roads. The rules regarding the provisionof access roads are regulated in Articles 667 and 668 of the Civil Code, which statethat the owner of the surrounded land can sue for access roads by providing faircompensation. This principle is in line with the social function of land, which shouldnot harm the interests of the wider community. If a dispute arises regarding accessroads, it can be resolved through litigation and non-litigation channels. The absenceof a specific legal product regulating the technical aspects of access road rights hasresulted in disputes being resolved through mediation. One of the main keys to thesuccess of dispute resolution through mediation in land disputes that will be usedas access roads is the good faith of the parties involved. This study not only discussesthe right to access roads for landowners who are surrounded but also discusses theresolution of land disputes through mediation in disputes over land that will beused as access roads in Kasepuhan Village, Batang Regency.